2022
DOI: 10.7759/cureus.29909
|View full text |Cite
|
Sign up to set email alerts
|

Granulomatosis With Polyangiitis Presenting With Diffuse Alveolar Hemorrhage: A Systematic Review

Abstract: Granulomatosis with polyangiitis (GPA) is a systemic disease that has variable clinical expression. GPA is the most common antineutrophilic cytoplasmic antibody (ANCA)-associated vasculitis (AAV). Diffuse alveolar hemorrhage (DAH) is one of the least common pulmonary manifestations in patients with GPA. DAH is clinically marked by hemoptysis, anemia, and diffuse alveolar infiltrates on imaging as well as hypoxemic respiratory failure. The diagnosis and treatment are challenging. Recommendations for ANCA-associ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 33 publications
0
5
0
Order By: Relevance
“…In those with renal dysfunction or pulmonary hemorrhage complicated by respiratory compromise, plasmapheresis should be considered. 25 GPA with salivary glands involvement has been reported rarely. In the present case, despite the previous evidence of arthritis, the occurrence of swelling and involvement of the parotid and submandibular glands along with the observation of the pulmonary nodule raised the suspicion of the occurrence of other autoimmune disorders.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In those with renal dysfunction or pulmonary hemorrhage complicated by respiratory compromise, plasmapheresis should be considered. 25 GPA with salivary glands involvement has been reported rarely. In the present case, despite the previous evidence of arthritis, the occurrence of swelling and involvement of the parotid and submandibular glands along with the observation of the pulmonary nodule raised the suspicion of the occurrence of other autoimmune disorders.…”
Section: Discussionmentioning
confidence: 99%
“…In GPA with a milder state, glucocorticoids combined with methotrexate are preferred. In those with renal dysfunction or pulmonary hemorrhage complicated by respiratory compromise, plasmapheresis should be considered 25 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Diagnosis of GPA is multifactorial, based on clinical manifestations, findings on high-resolution chest CT, positive ANCA labs, and histopathology showing necrotizing granulomatous inflammation [1,4,8]. Bilateral lung nodules in subpleural regions on chest CT and a rim of ground glass opacities (if diffuse alveolar hemorrhage is present) also suggest GPA [17,18]. Other common imaging findings include pleural effusions and tracheal/upper respiratory tract thickening leading to stenosis, which were the impetuses for our patient's admission.…”
Section: Discussionmentioning
confidence: 99%
“…Notable AAVs include granulomatosis with polyangiitis (GPA), microscopic polyangiitis (MPA), eosinophilic GPA, drug-induced vasculitis, and renal-limited vasculitis. Diffuse alveolar hemorrhage (DAH) is a serious clinical presentation that carries significant mortality in patients with AAV, with morbidity rates as high as 20% in GPA ( 2 ). Publications have suggested that this is most common in MPA with anti-myeloperoxidase anti-neutrophil cytoplasmic antibody, with an incidence of 12–19% ( 3 , 4 ).…”
mentioning
confidence: 99%